UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK KULIT NANAS (Ananas comosus. L) TERHADAP PERTUMBUHAN Ralstonia solanacearum - Astherix Putri Yudha; Ngadiani Ngadiani (UNUSA Press, 2018)
This study aims to determine the effectiveness of antibacterial pineapple peel extract (Ananascomosus. L) on Ralstonia solanacearum growth. Pineapple peel extract (Ananas comosus.L) containsantibacterial compounds of bromelin and tannin enzymes that are able to inhibit the growth of plantcausing bacteria, Ralstonia solanacearum. Ralstonia solanacearum bacteria will be given 5treatments with pineapple peel extract 10%, 30%, 60%, 100% and positive control Streptomicinsulfate 0.01%, each repeated 5 times. The test was performed by adding 100μl of Ralstoniasolanacearum suspension which was diluted into 15ml Tetrazolium chloride agar medium which wasgiven 100 ml of pineapple peel extract. The results showed that the treatment of pineapple peel extracthad a significant effect on the growth of Ralstonia solanacearum. The average number of treatedbacteria 60% (4x107 CFU), 100% (8x106 CFU) and Streptomicin sulfate 0.01% (4x106 CFU) wassignificant (P <0.01) higher than the number of bacteria treated by concentration 10% (1.79x108)and 30% (1.27x108). Consentration 100% pineapple peel extract (Ananas comosus.L) is the mosteffective in inhibiting the growth of Ralstonia solanacearum. Thus it can be concluded that pineapplepeel extract (Ananas comosus.L) is effective as an antibacterial Ralstonia solanacearum.